Paradigm Shift in Dendritic Cell-Based Immunotherapy: From in vitro Generated Monocyte-Derived DCs to Naturally Circulating DC Subsets - Wimmers, Florian; Schreibelt, Gerty; Sköld, Annette E.; Figdor, Carl G.; De Vries, I. Jolanda M. (Frontiers in Immunology, 2014)
Dendritic cell-based immunotherapy employs the patients’ immune system to fight neoplastic lesions spread over the entire body. This makes it an important therapy option for patients suffering from metastatic melanoma, which is often resistant to chemotherapy. However, conventional cellular vaccination approaches, based on monocyte-derived dendritic cells, only achieved modest response rates despite continued optimization of various vaccination parameters. In addition, the generation of monocyte-derived dendritic cells requires extensive ex vivo culture conceivably hampering the immunogenicity of the vaccine. Recent studies, thus, focused on vaccines that make use of primary dendritic cells. Though rare in the blood, these naturally circulating dendritic cells can be readily isolated and activated thereby circumventing lengthy ex vivo culture periods. The first clinical trials not only showed increased survival rates but also the induction of diversified anticancer immune responses. Upcoming treatment paradigms aim to include several primary dendritic cell subsets in a single vaccine as preclinical studies identified synergistic effects between various antigen-presenting cells.